EDUKASI PENGELOLAAN SAMPAH GUNA WUJUDKAN LINGKUNGAN SEHAT DI DAPUR MANAHAYU - Arista Fauzi Kartika Sari; Ibnu Zakaria; Galih Ilham Afif; Ryan Fazrin Ahmad; Bulharis Bulharis; Alivia Nur Yuana; Clarissa Frisma Adinda; Erni Eris Setiawati; Indi Rachmawati; Ulfa Syaidatina; Sarah Ahmad (Universitas Islam Malang, 2022)
A clean environment will reflect the conditions of the people who live in it. Environmental empowerment is a shared goal that must be created together as well. This environmental empowerment activity is carried out through the work program of the Candidate Undergraduate Service (KSM-T) of the Islamic University of Malang which is an activity based on community service to increase student empathy for the conditions of society and the environment. The candidate for the Bachelor of Service (KSM-T) at the Islamic University of Malang was held in the Kitchen Manahayu Dusun Sumbersari, Giripurno Village, Batu City, using the methods of socialization, education and mentoring and evaluation. This program has succeeded in helping environmental protection in order to reduce the impact of environmental pollution and be able to maintain a healthy, beautiful and clean environment. In addition, the waste that is sorted in the trash can makes it easier for the waste management process at the final level.